L'humour, reflet de la culture d'un peuple: l'exemple de la littérature populaire vietnamienne - Lo-Cicero, Minh Ha (2018)
Humorous and satirical stories in Vietnamese popular literature began during feudal times. The stories characterize the inequality of that society, which comprised two fundamentally opposed classes: the ruling Lords and the Serfs. Funny stories thrive when there is this type of social condition. In this way the Vietnamese Serfs created numerous stories to amuse themselves by ridiculing the bad habits and vices of the Lords and by exposing the injustice and oppression of the feudal regime. The humor of these stories has two opposite effects: the two classes are divided because the oppressive feudal yoke is denounced, but the Serfs are united through sharing the caustic humor which characterizes these stories. Humor reflects a people’s culture and is manifested through their language. In Vietnamese popular literature, humor is not always easy to understand if you are ignorant of the traditions, habits, culture and spirit of the country.